Legal Realism and Health Criminal Law Reform in the Era of Medical and Technological Advances - Nilamsari, Martina; Darma, I Made Wirya; Huzaif Mail, Syed Muhammad (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
Health criminal law faces evolving challenges driven by rapid technological advancements and shifting social dynamics. Issues such as medical malpractice, drug counterfeiting, patient data privacy, and equitable access to healthcare require legal frameworks that are both adaptive and rights-based. However, Indonesia's current legal regulations often fall short in addressing these complex realities, revealing a gap between normative provisions and practical implementation. This research analyses the challenges of enforcing health criminal law in the modern era through the lens of legal realism and proposes adaptive legal solutions. Utilising normative legal research, including statutory and conceptual approaches, the study examines primary, secondary, and tertiary legal materials to assess the responsiveness of existing regulations. The findings highlight legal uncertainty, weak enforcement mechanisms, and insufficient alignment with technological and ethical developments. The novelty of this study lies in offering an integrated framework based on legal realism that emphasises pragmatic and contextually informed legal reform. Proposed solutions include comprehensive regulatory reform, restorative justice approaches, professional capacity-building, transparent oversight mechanisms, clear standards of criminal liability, and stronger protections against drug counterfeiting and patient data breaches. The study emphasises the need to strike a balance between law enforcement and human rights protection in the context of technological innovation in healthcare.